Distribución de epífitas vasculares en matorrales costeros de Veracruz, México - Garcia-Franco, Jose G. (Instituto de Ecología, A.C., 1996)
The distribution of epiphytic species was studied on coastal sand dunes of La Mancha Coastal Research Station, Veracruz, Mexico. Eleven species of phorophytes were found, Randia laetevirens being the most important host (80.37 % of samples), followed by Diphysa robinioides (with only 7.48 % of samples). Six species of bromeliads and three species of mistletoes on sand dune shrubs and isolate trees were found. Tillandsia circinnata is the most abundant epiphyte followed by the parasite Phoradendron tamaulipense. Presence and abundance of epiphytes and parasites in sand dune system is probably determinated by characteristics (architecture, exposition time, distribution) of the phorophyte, by seed dispersal seasons (during the dry and windy season) of the epiphytes, as well as by sources of their propagules in the vicinity of the dunes.